RESEARCH ON EXTRACTION TECHNOLOGY TO IMPROVE YIELD AND QUALITY OF OIL FROM GAC ARIL (MOMORDICA COCHINCHINENSIS SPRENG L.) - Thuat, Bui Quang (Vietnam Journal of Science and Technology, 2012)
1. INTRODUCTIONGac (Momordica cochinchinensis Spreng L.) belonging to the family Cucurbitaceae is an indigenous Vietnamese fruit-bearing plant. Its fruit flesh contains 1 - 3 mm thick, red, soft, and sticky aril, which covers black seeds and makes up about 25% of the fruit weight [1].Gac aril has an oil content of about 38% - 40% (as related to absolute dry matter). This oil is a rich source of beta-caroten and lycopen, containing 128 mg%, and 170 mg% of each, respectively. The alpha-tocopherol content in the pulp was found to be 76.3 mg/g [2]. Because of its valuable constituents as mentioned above, Gac fruit oil is studied and used to create functional food and pharmaceutical products. A 30-day controlled supplementation trial carried out in Vietnam found that daily consumption of ‘‘xoi gac’’, a traditional Vietnamese sticky rice dish containing Gac aril, signiﬁcantly improved plasma levels of retinol, alpha-caroten, beta-caroten, and lycopen in pre-school children [3]. Researchers also investigated the potential of Gac fruit to prevent and treat cancers and vitamin A deﬁciency, where by juice extracted from dried Gac was found to reduce the tumour weights in mice by 23.6% [4]. The content of lycopen in Gac pulp as reported by this study (408 mg/g) is much higher than that usually found in tomatoes (about 25 mg/g) [5].Currently, Gac aril oil production is mainly carried out by traditional mechanical expression with a screw press, but  this method gives low yield and quality (especially in regard to the content of beta-caroten and lycopen). This paper describes a new method to obtain Gac aril oil with high extraction yield and oil quality.